Prevalence of long acting and permanent contraceptive methods among married population in a selected rural community - Uddin, Md Nasir; Ara, Rowshan (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Contraception is an essential method for reducing fertility rate. The long-acting and permanent contraceptive methods can adversely affect the health of the mother and the child. Objectives: The study was conducted to assess the prevalence of long acting and permanent contraceptive methods among married population in a selected rural community of Gazipur District. Methods: This was a descriptive type of cross sectional study conducted to explore the prevalence of long acting and permanent contraceptive methods among the adult married population in the rural community of Mulaid village under Telihati union of Sreepur Upazilla under Gazipur District. Sample size was 372 and purposive sampling technique was followed for data collection which was done by face to face interview using semi structured questionnaire. The data was analyzed by SPSS 16 software. Results: Majority (64.5%) of the respondents were female. Highest number of male respondents (44.7%) were in 20 to 30 years age group and highest number of the female respondents (45.0%) were in 15 to 25 years age group. Maximum male respondents (18.9%) were educated up to secondary level and maximum female respondents (29.6%) were educated up to secondary level. Out of total 372 respondents, 92% (344) were aware about contraceptive methods and 74.2% (277) of them used different kinds of contraceptive methods. 93 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 Among them 75% (209) used short acting contraceptives, while 17% (48) used long acting contraceptives and 8% (21) used permanent methods. Out of 48 long acting contraceptive method users, maximum (64.6%) used Injection, 29.2% (14) used Implants and 6.2% (3) used I.U.C.D. Among permanent contraceptive methods users, 81.0% (17) used tubectomy and 19% (4) used vasectomy. Out of all Long Acting and Permanent Contraceptive Methods (LAPM) users, percentage of injection was 45% (27), I.U.C.D 5% (3), implant 20% (12) tubectomy 23.33% (14) and vasectomy 6.6% (4). Among the long acting method users(n=48), percentage of injection and implant usage were highest (injection: 60%--18, implant: 26.6%--8) among the respondents having more than two children and percentage of I.U.C.D. usage was highest i.e. 7.6%(3) among the respondents with two or less than two living children. Regarding side effects, among 66.6%(32) of long acting contraceptive method users, maximum i.e. 37.5%(12) mentioned amenorrhea and rest of the respondent(20) mentioned different side effects such as excessive menstruation, irregular menstruation, weight gain etc. Conclusion: Use of long term and permanent contraceptive methods among people is increasing day by day and this use increases with higher level of education, awareness and social and economic status. Still there is a need to intensify information; education, communication activities and this motivate the people to adopt long term and permanent contraceptive methods. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21846 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013